On the performance of algebraic reconstruction technique algorithm for microwave imaging - Dhani Elevani (2018)
© 2016 IEEE. A microwave imaging system for scanning the presence of cancer in the body is designed. The system uses a pair of dipole antennas as a transmitter and a receiver at frequency of 3 GHz based on Algebraic Reconstruction Tecnique (ART) algorithm. Two types of numerical phantom are used for validating the image reconstruction system, a cylindrical phantom and a Shepp-Logan phantom. The reconstructed image and its histogram show that the system is successful in representing the tissue characteristics of the phantoms for identifying the presence of tumorous tissue.